Effects from geothermal effluent on periphyton and invertebrate assemblages in NE-Iceland - Sigurður Óskar Helgason 1990- (2017)
Geothermal energy utilization in Iceland is a growing industry in order to fulfil constantly growing energy demand. One of Iceland’s geothermal power plant is located in NE-Iceland, the 60 MW Krafla geothermal Power Plant, which currently utilizes energy from 18 boreholes. The primary objective of this study was to investigate possible effects from the effluent from a geothermal energy utilization on the aquatic ecosystem in the stream Hlíðardalslækur. I studied both spatial and temporal variations in the benthic algae and Cyanobacteria assemblages in three geothermally spring-fed streams in the Krafla geothermal area. The diversity and density of invertebrates within the same sites were also studied in September 2015 and January 2016. Periphyton accrual responses to four different nutrient enrichments were also tested in the fall of 2015. Algae and Cyanobacteria assemblage varied significantly between sampling sites in regards to dominating genera, density and diversity. Relatively high periphyton densities characterized upstream reaches from the power plant, along with the numbers of genera and diversity being relatively high as well. Endosymbiotic diatoms (i.e. N2-fixing genera such as Epithemia and Rhopalodia) and non-N2-fixing diatoms (Caloneis, Nitzschia and Navicula) characterized the algae communities, along with the presence of Chlorophyta (Stigeoclonium and Klebsormidium). The N2-fixing Cyanobacteria, mainly Anabaena, grew spatially upstream, mainly on cobbles near the stream banks. Invertebrates were in low densities and their diversity was also rather poor. The periphyton accrual was significantly increased by adding nitrogen to the streams. There were significant changes in the algae and Cyanobacteria assemblage downstream to the power plant where microbial mats covered the stream bottom. These mats consisted only of heterocystous (N2-fixing) and non-heterocystous Cyanobacteria, as neither diatoms nor green algae seemed to thrive in that habitat. N2-fixing genera, Anabaena and Calothrix, ...